OUTDOOR GAMES IN YOUTH’S PHYSICAL EDUCATION - Boldyreva, V.B.; Keyno, A.Y.; Kuzmenko, M.V. (Tambov University Review. Series: Humanities, 2016)
An important task for the teacher is to educate students in care, correctness, willingness to help, teamwork, honesty, unselfishness, criticality of goodwill in respect of all people. A good means of educating these qualities can serve a variety of outdoor games and competitions. Fulfilling the role of team captain games, assistant (teacher), leading, defender, forward, students learn not only to meet their own responsibilities, but also to control the actions of other people, organize them to address common problems. An important place in the classroom for outdoor games takes gaming method that allows to distract from dealing with sometimes continuous repetitive work in the classroom, increase their emotions, make them variety. The task of the teacher is that of a plurality of mobile games appropriate to choose exactly the game, which would help as soon as possible to increase the emotional burden and help mastering and securing the necessary knowledge and skills, as well as the development and strengthening of bones and ligaments, muscle system and the formation of the correct figures involved.